Negotiating Trust in the Digital Marketplace: Community Narratives of Informal Tourism in Indonesia - Utama Dewayani, Eka Kadharpa (Centre for Tourism Studies and Journal Publication of Sekolah Tinggi Pariwisata Mataram, 2024)
The rise of digital platforms has transformed the organization of tourism economies, particularly in contexts where informal enterprises play a dominant role. In Indonesia, small-scale actors such as homestay owners, local guides, and craft producers increasingly rely on platforms like Airbnb, Instagram, and TikTok to market services and connect with travelers. Yet, while these platforms promise visibility and access to global markets, they also create new challenges of trust, dependence, and regulation. This study explores how informal tourism actors in Bali and Yogyakarta negotiate trust in the digital marketplace. Using qualitative methods, including in-depth interviews with homestay operators, local vendors, and community-based guides, as well as participant observation of online marketing practices, the research examines how digital tools mediate relationships between hosts and guests. Thematic analysis reveals that platforms are valued as vital gateways to income diversification, but they are also perceived as unpredictable, extractive, and difficult to control. Narratives highlight strategies of trust-building through personal storytelling, cultural authenticity, and community reputation, while also voicing concerns about algorithmic visibility, unfair reviews, and platform dependency. By foregrounding local voices, the study contributes to critical debates on digital tourism economies, informality, and community resilience in the Global South.